Microfinance and its relationship with the development of the agricultural sector in Colombia (Revista "Boletín el Conuco", 2026)
Objective: To determine whether there is a relationship between microfinance loans and the economic development of the agricultural sector, as well as to understand the factors that have influenced the financing of small agricultural producers through microfinance. Methodology: A simple linear regression model was estimated with the agricultural sector’s GDP in the department of Cauca as the dependent variable and Banco Agrario’s microcredit portfolio as the independent variable. Additionally, interviews were conducted with administrative staff members of microfinance service providers and with an agricultural microentrepreneur. Results: A positive correlation was identified between microfinance loans and the economic development of the agricultural sector in the Cauca department. Furthermore, challenges that hinder farmers' access to microcredit were recognized, which relate directly to the requirements set by microfinance institutions as well as farmers' ability to repay loans and provide collateral. Conclusions: Microcredit is an effective tool for overcoming access barriers to financing for micro and small agricultural entrepreneurs; however, these barriers must be addressed to broaden its reach..
Keywords: Microfinance; Economic development; Financing; Microentrepreneurs; Agricultural sector